Correlation between Skinfold Thickness and Total Daily Dose of Insulin in Patient with Type 2 Diabetes Mellitus in Dr Soetomo General Hospital - Larasati, Amilia Putri; Prajitno, Jongky Hendro; Purwanto, Bambang (Universitas Airlangga, 2023)
Introduction: Type 2 diabetes mellitus (T2DM) is a non-communicable disease with a high prevalence in Indonesia. T2DM is caused by insulin resistance and relative insulin deficiency. One of the therapy for T2DM is insulin administration which is injected into the subcutaneous tissue. The absorption of insulin in the subcutaneous tissue is influenced by many factors, one of which is the thickness of subcutaneous fat. This study aimed to determine the correlation between the skinfold thickness of T2DM patients with the total daily dose of insulin needed every day. Methods: This was an observational analytic study using a cross-sectional design to analyze the correlation between subcutaneous fat thickness represented by skinfold thickness and the total daily dose of insulin of T2DM patients. Measurement of skinfold thickness was carried out on the triceps using a skinfold caliper. Data on the patient's total daily dose of insulin were obtained from medical records.Results: A total of 53 patients were included in this study. The patient's mean triceps skinfold thickness was 26.29±8.72 mm. The mean total daily dose of insulin was 40.96±18.01 IU. The results of the Spearman Rank correlation test showed a significant correlation between skinfold thickness on the triceps and the patient's total daily dose of insulin (p<0.05). Conclusion: The higher the skinfold thickness, the greater the dose of insulin needed by the patient.